(untitled) (Al-Aasar, 2025)
Tele is an English word meaning remote, remote and especially used in the names of devices that can be used to count or record remote results etc. The most important and innovative technology of modern era without which cannot move forward not a single step. Only the audience is recognized through vision. This play is written and performed specifically for electronic media. Teledrama is not only a source of entertainment but it also plays an important role in awakening social consciousness, promoting moral values ​​and highlighting various aspects of human life. It was the era of modern technology that made Urdu drama recognized worldwide. Pakistani TV dramas made their unique and strong recognition. It seemed to build. Its basic purpose was to highlight the spirit of indifference in the younger generation – many dramas and serials were produced under this purpose- The rise of thematic and national dramas (1980s-1990s) This period was marked by thematic and military themes. These dramas instill the spirit of patriotism, discipline and character building in the younger generation, while these works send a message of unity, sacrifice and national unity in society. Those military dramas are not mere stories, but reflect an ideology, an era and the collective consciousness of the nation.